PENGARUH HARGA, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA BATIK IWAN TIRTA COLLECTION DI GRAND INDONESIA - Nurul Afipah; Simatupang, Lucy Nancy (Pasca Sarjana Universitas Satya Negara Indonesia, 2024)
This study aims to identify the effect of price, product quality and location on consumer purchasing decisions at the Iwan Tirta Collection in Grand Indonesia simultaneously or partially. The data used is primary data collected by distributing questionnaires to 100 respondents who have visited the Iwan Tirta Collection. Quantitative method and the results of this study are based on respondents' answers using a Likert scale. The analytical method used in this study is multiple linear regression test, F test, t test and the coefficient of determination. The results of this study indicate that by F test (simultaneous) there is a significant influence between Price, Product Quality and Location on Consumer Purchase Decisions. t test (partial) shows that price has a significant effect on purchasing decisions, product quality has significant and significant influence on purchasing decisions, and location has no significant effect on purchasing decisions.